Facies and statistical analyses of a crevasse-splay complex at the Tomisławice opencast lignite mine in central Poland - Dziamara, Mariusz; Kaczmarek, Paweł; Klęsk, Jakub; Wachocki, Robert; Widera, Marek (Geologos, 2023)
The studied crevasse-splay complex, situated within the 1st Mid-Polish lignite seam (MPLS-1), ranks amongst the best-developed and most readily accessible for direct research of all hard coal and lignite occurrences worldwide. The sandy-coaly sediments constituting it required a number of field and laboratory tests. However, the present article focuses solely on sedimentological and statistical analyses of sediments along a selected key section, the most important results of which are presented below. First of all, data obtained in previous sedimentological studies have been confirmed, in that individual segments of this complex represent both subaerial and subaqueous types of crevasse splays. On the one hand, their sediments are characterised by an extremely high content of coalified organic matter, reaching 20–40 wt.% in some samples; on the other, these crevasse splays are composed of fine sands with a median and mean grain size of 0.15 mm. In addition, the remaining statistical parameters (standard deviation, skewness and kurtosis) indicate a very good sorting of these sands, no significant so-called ‘tails’ and a better sorting close to the sediment mean grain size value, respectively.